Fig. 4 in Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica - Kuzmina, T. A.; Dykyy, I. V.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zenodo, 2021)
Fig. 4. Cluster analysis of the similarity between the helminth communities in five teleost fish species off the area of the UAS "Akademik Vernadsky", Argentine Islands, and West Antarctica. Published as part of Kuzmina, T. A., Dykyy, I. V., Salganskij, O. O., Lisitsyna, O. I., Korol, E. M. & Kuzmin, Yu. I., 2021, Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica, pp. 251-264 in Zoodiversity 55 (3) on page 259, DOI:10.15407/zoo2021.03.251, http://zenodo.org/record/6455979